Pengaruh Brand Image, Kualitas Produk, dan Online Customer Review Terhadap Keputusan Pembelian Produk Wardah - Nabila Nuzulia Ramadhany; Kartini Isikomah (Trending: Jurnal Manajemen dan Ekonomi, 2024)
This study aims to determine the impact of product quality, brand image, and online customer reviews on the purchase decisions of female customers of the Wardah brand in the JaBoDeTaBek area. There were a hundred respondents in the sample for this quantitative study. The sampling strategy uses the lemeshow formula and a non-probability sampling technique called purposive sampling. Using the Likert scale to measure the level of consent, the questionnaires were distributed as part of the data collection process. SPSS Version 22 and Microsoft Excel 2019 are used to examine the collected data. According to the study's findings, factors such as brand image and online customer reviews have little or no influence on purchasing decisions, but product quality variables have a positive and significant impact. The results of the simultaneous analysis showed that the purchase decision was positively influenced by the simultaneous and tangible effects of the brand image, product quality, and online customer reviews.